2014
DOI: 10.1111/pan.12547
|View full text |Cite
|
Sign up to set email alerts
|

Sedation monitoring during open muscle biopsy in children by Comfort Score and Bispectral Index – a prospective analysis

Abstract: Bispectral Index provides an additional helpful tool to guide sedation/analgesia in minor surgical procedures in children. BIS values ≤60 correlated with sufficient depth of sedation and prevented unintended awareness. Additionally, BIS measurement allowed for distinct regulation of depth of sedation without prolonged sedation/analgesia due to unintended overdose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
(30 reference statements)
1
21
0
Order By: Relevance
“…Different authors validated the CS in PICU (Bear & Ward‐Smith, ; Brunow de Carvalho, Lucas da Silva, Paulo, Fonseca, & Belli, ; Courtman, Wardurgh, & Petros, ; Froom et al., ; Ista et al., ; Lamas et al., ; Nievas, Spentzas, & Bogue, ; Triltsch et al., ; Tschiedel, Müller, Schara, Felderhoff‐Müser, & Dohna‐Schwake, ). Some others authors also assessed the comfort of neonates by using the CS (Blauer, ; Cury, Martinez, & Carlotti, ; Franck, Ridout, Howard, Peters, & Honour, ; Van Dijk et al., ; Wielenga, de Vos, de Leeuw, & de Haan, ), Comfort Neo Scale (Monique Van Dijk et al., ), Modified Comfort Scale (Gjerstad, Wagner, Henrichsen, & Storm, ; Lee & Young, ) and Adapted Comfort Scale (Caljouw et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Different authors validated the CS in PICU (Bear & Ward‐Smith, ; Brunow de Carvalho, Lucas da Silva, Paulo, Fonseca, & Belli, ; Courtman, Wardurgh, & Petros, ; Froom et al., ; Ista et al., ; Lamas et al., ; Nievas, Spentzas, & Bogue, ; Triltsch et al., ; Tschiedel, Müller, Schara, Felderhoff‐Müser, & Dohna‐Schwake, ). Some others authors also assessed the comfort of neonates by using the CS (Blauer, ; Cury, Martinez, & Carlotti, ; Franck, Ridout, Howard, Peters, & Honour, ; Van Dijk et al., ; Wielenga, de Vos, de Leeuw, & de Haan, ), Comfort Neo Scale (Monique Van Dijk et al., ), Modified Comfort Scale (Gjerstad, Wagner, Henrichsen, & Storm, ; Lee & Young, ) and Adapted Comfort Scale (Caljouw et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…To provide a second and more objective instrument we added BIS to the sedation protocol. We are fully aware that the use of BIS is not only limited due to its interindividual differences [29], but also reflects sedation depth with an uncertain delay of seconds. As sleep induction generally is a short process of a few minutes the delay of BIS might falsify the documented time until sleep onset to a relevant extent.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the Bispectral Index (BIS) provides an objective method to monitor the patient's level of consciousness via electroencephalography (EEG)signal-analysis. Although its benefit is controversially discussed [22] it still provides objective data with good correlation to clinical sedation scores [8,20,23,24,27], and its use is safe [29].…”
Section: Introductionmentioning
confidence: 99%
“…This is also true if sedation with propofol and remifentanil is monitored using BIS [31]. In particular, sedation for open muscle biopsy in children under sedation/analgesia with propofol and remifentanil and advanced sedation monitoring using bispectral index (BIS) and Comfort Score (CS) is safe [28].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the benefit of additional BIS monitoring is controversial because many factors such as impedance, stimulation, medication and electrical interferences can influence score measurement, and optimal ranges for BIS scores still cannot be clearly defined and are different according to individual [21]. Nevertheless several studies have shown that BIS ranges between 50 and 70 [11,16,28] are safe. In deep sedation (as in muscle biopsies), the utility of CS alone is limited because adequately anesthetized and oversedated patients may clinically appear similar.…”
Section: Introductionmentioning
confidence: 99%